Fanconi Anemia Mesenchymal Stromal Cells-Derived Glycerophospholipids Skew Hematopoietic Stem Cell Differentiation Through Toll-Like Receptor Signaling. (24th July 2015) - Amarachintha, Surya; Sertorio, Mathieu; Wilson, Andrew; Li, Xiaoli; Pang, Qishen
Abstract: Fanconi anemia (FA) patients develop bone marrow (BM) failure or leukemia. One standard care for these devastating complications is hematopoietic stem cell transplantation. We identified a group of mesenchymal stromal cells (MSCs)-derived metabolites, glycerophospholipids, and their endogenous inhibitor, 5-(tetradecyloxy)−2-furoic acid (TOFA), as regulators of donor hematopoietic stem and progenitor cells. We provided two pieces of evidence that TOFA could improve hematopoiesis-supporting function of FA MSCs: (a) limiting-dilution cobblestone area-forming cell assay revealed that TOFA significantly increased cobblestone colonies in Fanca−/− or Fancd2−/− cocultures compared to untreated cocultures. (b) Competitive repopulating assay using output cells collected from cocultures showed that TOFA greatly alleviated the abnormal expansion of the donor myeloid (CD45.2+Gr1+Mac1+) compartment in both peripheral blood and BM of recipient mice transplanted with cells from Fanca−/− or Fancd2−/− cocultures. Furthermore, mechanistic studies identified Tlr4 signaling as the responsible pathway mediating the effect of glycerophospholipids. Thus, targeting glycerophospholipid biosynthesis in FA MSCs could be a therapeutic strategy to improve hematopoiesis and stem cell transplantation. Stem Cells 2015;33:3382–3396